2021
DOI: 10.2174/2215083806999200720164432
|View full text |Cite
|
Sign up to set email alerts
|

Yoga can Alter the Autonomic Neural Activity: A Critical Analysis

Abstract: Background: Modern lifestyle leads a greater psychotechnological stress and it results increase of autonomic imbalances. This predicts disturbance of the normal mental state and cognition. The current researchers found clear relationship between yoga practice and parasympathetic dominance. Objectives: The purpose of the review study was to analyze the scientific literatures related to yoga and autonomic neural responses. Methods: Researchers collected scientific evidences through electronic online database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Researcher found that referees who reported a low satisfaction of social support were significantly more likely to report symptoms of stress and anxiety disorder [17]. Pressure to make decisions in front of large crowd is another potential stressor [18,30,31]. These two stressors can impair attention executive control [23], depending on physical fitness and individual vulnerability or resilience to situational pressure [32].…”
Section: Discussionmentioning
confidence: 99%
“…Researcher found that referees who reported a low satisfaction of social support were significantly more likely to report symptoms of stress and anxiety disorder [17]. Pressure to make decisions in front of large crowd is another potential stressor [18,30,31]. These two stressors can impair attention executive control [23], depending on physical fitness and individual vulnerability or resilience to situational pressure [32].…”
Section: Discussionmentioning
confidence: 99%